Factors associated with awareness of literate mothers about newborn screening: a cross-sectional study from a low-middle-income country - Majid, Hafsa; Lena Jafri; Jameel Farooqui, Arsala; Ahmed, Sibtain; Khan, Zaib Un Nisa; Habib Khan, Aysha (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the awareness level of literate mothers regarding newborn screening programmes, and to evaluate the associated factors. Method: The descriptive, cross-sectional study was conducted at the Section of Chemical Pathology, Department of Pathology and Laboratory Medicine, Aga Khan University, Karachi, from January to September 2021, and comprised mothers aged 18 years or more. Data was collected using a structured questionnaire about newborn screening, and the subjects were compared in terms of age, residential background, education and parity. Data was analysed using SPSS 23. Results: Of the 1016 responses, 896(88.2%) were analysed. The mean age of the sample was 37.7±10.87 years. There were 470(52.4%) mothers aged 31-45 years, 859(95.87%) were from urban areas, 751(84%) had a graduate degree, 652(72.7%) were multiparous and had 824(91.9%) had healthy children. Overall, 386(43%) mothers had awareness of newborn screening programmes. The main factors associated with awareness were age, education, primiparity, having healthy children, and province of residence being Sindh and Punjab (p<0.05), while the urban-rural divided was not a significant factor (p=0.737). Cost of healthcare 417(46.5%) and lack of awareness among physicians 356(39.7%) were identified as the main challenges in establishing newborn screening services in the country. Conclusion: The awareness among mothers about newborn screening programmes was general low among the subjects studied. Key Words: Newborn screening, Inborn errors of metabolism, Public health, Knowledge attitude and practice survey, Metabolomics.